CpSmt3, an ortholog of small ubiquitin-like modifier, is essential for growth, organelle function, virulence, and antiviral defense in Cryphonectria parasitica - Li, Shuangcai; Chen, Fengyue; Wei, Xiangyu; Yuan, Luying; Qin, Jiayao; Li, Ru; Chen, Baoshan (Frontiers in Microbiology, 2024)
SUMOylation is an important post-translational modification that regulates the expression, localization, and activity of substrate proteins, thereby participating in various important cellular processes such as the cell cycle, cell metabolism, gene transcription, and antiviral activity. However, the function of SUMOylation in phytopathogenic fungi has not yet been adequately explored. We report the characterization of a SUMO protein, designated CpSmt3, in Cryphonectria parasitica, the fungal pathogen responsible for chestnut blight. Deletion of the CpSmt3 gene resulted in defects in mycelial growth and hyphal morphology, suppression of sporulation, attenuation of virulence, weakening of stress tolerance, and elevated accumulation of hypovirus dsRNA. The ∆CpSmt3 deletion mutant also had increased mitochondrial ROS, swollen mitochondria, excess autophagy, and thickened cell walls. Using affinity pull-down assays, about 500 putative SUMO substrate proteins were identified, among which many were implicated in the cell cycle, ribosome, translation, and virulence. Proteomics and SUMO substrate analyses further revealed that deletion of CpSmt3 reduced the accumulation of CpRho1, an important protein that is involved in TOR signal transduction. Silencing of CpRho1 resulted in a phenotype similar to that of ΔCpSmt3, while overexpression of CpRho1 could partly rescue some prominent defects in ∆CpSmt3. Together, these findings demonstrate that SUMOylation by CpSmt3 is vitally important and provide new insights into the SUMOylation-related regulatory mechanisms in C. parasitica.